1994
DOI: 10.1126/science.7939682
|View full text |Cite
|
Sign up to set email alerts
|

Internal Lysine Palmitoylation in Adenylate Cyclase Toxin from Bordetella pertussis

Abstract: A number of bacterial protein toxins, including adenylate cyclase (AC) toxin from Bordetella pertussis, require the product of an accessory gene in order to express their biological activities. In this study, mass spectrometry was used to demonstrate that activated, wild-type AC toxin was modified by amide-linked palmitoylation on the epsilon-amino group of lysine 983. This modification was absent from a mutant in which the accessory gene had been disrupted. A synthetic palmitoylated peptide corresponding to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
200
1
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(207 citation statements)
references
References 34 publications
3
200
1
2
Order By: Relevance
“…There have been few reports describing MS/MS characterization of acylated proteins or peptides. In identifying the novel palmitoylations on internal lysine residues in adenylate cyclase toxins (ACT) [34,35], Hackett and coworkers showed that the amide-linked palmitoyl groups are retained on the backbone fragments (b, y) during CAD in a triplequadrupole mass spectrometer.…”
Section: Ecd Versus Cadmentioning
confidence: 99%
“…There have been few reports describing MS/MS characterization of acylated proteins or peptides. In identifying the novel palmitoylations on internal lysine residues in adenylate cyclase toxins (ACT) [34,35], Hackett and coworkers showed that the amide-linked palmitoyl groups are retained on the backbone fragments (b, y) during CAD in a triplequadrupole mass spectrometer.…”
Section: Ecd Versus Cadmentioning
confidence: 99%
“…In support of this decision, studies of other proteins have shown that sites of palmitoylation in vivo and in vitro are equivalent (Bizzozero et al, 1987;Gutierrez and Magee, 1991;Stanley et al, 1994). Different methodologies for protein structure analysis have been used to identify palmitoylated amino acids (Papac et al, 1992;Weimbs and Stoffel, 1992;Bizzozero et al, 1994a;Hackett et al, 1994 (Ozols, 1984), necessitating the use of gel filtration on Sephadex LH60. Similar problems with recovery of palmitoylated peptides from HPLC columns have been described in other studies (Ovchinnikov et al, 1988 Palmitoylated Cysteine Residues of ea-Tubulin Luduefia and Roach (1981) determined that nondenatured a-and ,B-tubulin from brain, in the form of heterodimers, each contain three or four cysteine residues that are accessible for alkylation, implying that these cysteine residues are at the surface of the molecules.…”
Section: Proteinsmentioning
confidence: 99%
“…Cysteine residues are the primary sites of palmitoylation. However, serine, threonine, and lysine residues may also be palmitoylated (for review, see Bizzozero et al, 1994b;Hackett et al, 1994;Stanley et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The CyaA toxin is synthesized as an inactive precursor, proCyaA, which is converted into the active toxin form (CyaA) on specific acylation of two lysine residues (26,27). Then CyaA is secreted across the bacterial envelope by a dedicated type I secretion machinery and binds to the CD11b/CD18 integrin expressed by a subset of leukocytes including neutrophils, macrophages, and dendritic cells (22,(28)(29)(30).…”
mentioning
confidence: 99%